REPAIR OF VACUUM CLEANER AS A MOSQUE CLEANING TOOL AT AL-MADINAH AL-MUNAWWAROH PERUM MOSQUE. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI WEST JAVA: PERBAIKAN VACUM CLEANER SEBAGAI ALAT KEBERSIHAN MASJID DI MASJID AL-MADINAH AL-MUNAWWAROH PERUM. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI JAWA BARAT - Daud Surbakti; Dolok Th Purba; Rivaldi Rivaldi (Yayasan Education and Social Center, 2022)
A vacuum cleaner or mosque vacuum cleaner is a tool that uses an air pump to create an empty state to suck up dust and dirt, usually from floors and carpets. Most homes and places of worship with carpeted floors in developing countries have a vacuum cleaner for cleaning. Dirt is collected by a filtering system or cyclone and then disposed of. Vacuum cleaners are generally used to suck up dust or dirt, while the function of the mosque is to clean carpets and floors